Modernization of System Architectures to support Digital Transformation - Leon, Pablo Luiz; Horita, Flávio (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2020: Companion Proceedings of the 16th Brazilian Symposium on Information SystemsDO - 10.5753/sbsi.2020.13128, 2020)
With the widespread use of technology, companies and the government have used technologies to enable the digital transformation of products and services demanded by society. However, the decentralization of systems becomes important to create new solutions and / or services for users with a more connected and real-time experience. There are two challenges: 1) how to decentralize existing legacy systems to provide a technology solution that meets the new needs of users in this more digital society; and 2) how to create a systems architecture that addresses the characteristics inherent in digital transformation. In this sense, this project proposal aims to present an approach to modernize legacy systems in order to converge business in a digital transformation scenario.